(untitled) (Research, Society and Development, 2020)
Objective: To portray the possible multifactorial impacts due to the social distance in the daily life of the elderly. Methodology: Refers to an experience report with a qualitative approach and descriptive character about the participant observation regarding the perception of one of the researchers in relation to the maternal grandparents domiciled during the quarantine due to COVID 19. Results: It was noted that the elderly tend to suffer biopsychosocial, spiritual and environmental impacts due to social detachment, if they have not adopted measures to promote comprehensive health, with the prevention of physical inactivity through the cultivation of vegetables and physical activities, whether at home and / or in uncrowded environments. Discussion: It was found that coping and resilience are psychological aspects that are likely to develop, even in a context of crisis. Final considerations: The sensitive view of the senescent public is important, since the impacts of the pandemic can permeate the whole subject, moved by the potential to coping the situations experienced in this process, showing the resilience.